2014
DOI: 10.1177/0269215514556087
|View full text |Cite
|
Sign up to set email alerts
|

Cortical vs. afferent stimulation as an adjunct to functional task practice training: a randomized, comparative pilot study in people with cervical spinal cord injury

Abstract: Meaningful improvements in aspects of hand-related function that persisted at least 30 minutes after intervention were observed with transcutaneous electrical nerve stimulation and transcranial direct current stimulation, when combined with functional task practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 34 publications
2
59
0
2
Order By: Relevance
“…The finding that FTP + PNSS was associated with improvements in precision grip strength confirms the conclusions of prior smaller studies in persons with tetraplegia that have assessed the effects of this intervention on precision grip strength, but only in the weaker hand (12, 19). Imaging studies in neurologically healthy participants have shown that precision grip is associated with bihemispheric activation of numerous motor and sensory cortical regions, while power grip is associated primarily with activation of contralateral activation of the primary motor and sensory cortices (51).…”
Section: Discussionsupporting
confidence: 85%
“…The finding that FTP + PNSS was associated with improvements in precision grip strength confirms the conclusions of prior smaller studies in persons with tetraplegia that have assessed the effects of this intervention on precision grip strength, but only in the weaker hand (12, 19). Imaging studies in neurologically healthy participants have shown that precision grip is associated with bihemispheric activation of numerous motor and sensory cortical regions, while power grip is associated primarily with activation of contralateral activation of the primary motor and sensory cortices (51).…”
Section: Discussionsupporting
confidence: 85%
“…[15][16][17][18] Studies of rTMS and transcranial direct cortical stimulation are also based on patients with preserved voluntary activity in the muscles under investigation. 11,12,18 PAS induces plasticity in humans without concomitant effort by the subject; 4 we thus hypothesized that long-term PAS could be a technique that could affect also those muscles which are fully paralyzed.…”
Section: Introductionmentioning
confidence: 99%
“…The use of tDCS has led to improvements in pinch force, manual dexterity, and force modulation when combined with repetitive practice [18]. Other study reported that stimulation intensity affects functional outcomes when tDCS was delivered at rest: increased corticospinal excitability to affected muscles was obtained when using 2 mA stimulation, but not 1 mA, in nine chronic SCI patients [19].…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 98%
“…This technique is still in the early stage. To our knowledge, just seven studies have examined improvements in motor function after SCI related to the use of tDCS: four studies evaluated its effect on upper limb function [18][19][20][21] and three studies evaluated the tDCS effect on lower limb function and gait [22][23][24]. All these studies used anodal stimulation and showed improvements in upper and lower limb motor function.…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 99%